Should the Government Quality Control Agency Replace Community Health Center Accreditation? The Concept of Third Party with Metaregulation and Control Strategies - Haunan, Muhammad Hafiz; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: Community health center accreditation in Indonesia is a method used to ensure that health care facilities perform continuous quality improvement. However, the efficacy of this method is still debatable. Many community health centers focus only on obtaining accreditation certificates without ensuring substantial quality improvement. The lack of empirical evidence supporting the claim that accreditation ensures quality improvement indicates the need for alternative solutions for quality control. Method: This study uses a Third Party approach by employing two policy strategies, namely metaregulation and control strategies. This study compares Indonesian practice with the quality control model implemented by the Care Quality Commission (CQC) in the UK and the Food and Drug Administration (BPOM) in Indonesia. The policies and impacts of the supervision conducted by these independent bodies are analyzed. Results: The analysis shows that the existence of an independent government quality control body can be more effective in ensuring continuous quality improvement than the community health center accreditation system. Case studies of CQC in the UK and BPOM in Indonesia show that regulatory agencies with executive authority are able to provide strict supervision and decisive action against providers who do not meet standards. The implementation of metaregulation and control strategies by government quality oversight bodies can encourage health centers to be more proactive in conducting continuous quality improvement. Supervisory bodies that are directly accountable to the central government can reduce interventions from interested parties, ensuring objectivity and effectiveness of supervision. Conclusion: Replacing the accreditation of community health centers with a Government Quality Control Agency that is independent and has executive authority can be a solution to ensure continuous quality improvement of health services in community health centers. The implementation of metaregulation and control strategies in the Third Party concept will create a more effective and sustainable regulatory environment. Thus, monitoring the quality of health services will be more assured, not only limited to meeting formal standards, but also ensuring continuous improvement in the practice of health services at community health centers.